Biogeography of Tick-Borne Bhanja Virus (Bunyaviridae) in Europe. (21st December 2009) - Hubálek, Zdenek
Abstract : Bhanja virus (BHAV) is pathogenic for young domestic ruminants and also for humans, causing fever and affections of the central nervous system. This generally neglected arbovirus of the family Bunyaviridae is transmitted by metastriate ticks of the genera Haemaphysalis, Dermacentor, Hyalomma, Rhipicephalus, Boophilus, and Amblyomma . Geographic distribution of BHAV covers southern and Central Asia, Africa, and southern (partially also central) Europe. Comparative biogeographic study of eight known natural foci of BHAV infections in Europe (in Italy, Croatia, Bulgaria, Slovakia) has revealed their common features. (1) submediterranean climatic pattern with dry growing season and wet mild winter (or microlimatically similar conditions, e.g., limestone karst areas in central Europe), (2) xerothermic woodland-grassland ecosystem, with plant alliances Quercetalia pubescentis, Festucetalia valesiacae, and Brometalia erecti, involving pastoral areas, (3) presence of at least one of the tick species Haemaphysalis punctata, Dermacentor marginatus, Rhipicephalus bursa, and/or Hyalomma marginatum, and (4) presence of≥ 60% of the 180 BHAV bioindicator (157 plant, 4 ixodid tick, and 19 vertebrate spp.). On that basis, Greece, France (southern, including Corsica), Albania, Spain, Hungary, European Turkey, Ukraine (southern), Switzerland (southern), Austria (southeastern), Germany (southern), Moldova, and European Russia (southern) have been predicted as additional European regions where BHAV might occur.